The Development of Multimodal-Based Natural Science Teaching Materials to Improve the Science Literacy of Class IV at MI Masjid Al Akbar Surabaya - Chasan Ashari; Neni Mariana; Widiasih (Jurnal Penelitian Pendidikan IPA, 2025)
The results of field studies showed that the natural science literacy of students in Indonesia was still low. Indonesia’s performance in science literacy assessments like PISA has shown the need for improvement due to factors like limited resources, inadequate facilities, and uninspiring teaching materials that are not oriented toward the science literacy component. This study focused on the effectiveness of the use of textbook-oriented provisioning capability in science literacy by using multimodal learning materials. The textbook’s development method used a 4D model (define, design, development, and disseminate) to write. Textbook design, which was applied to the topic of “Animal Life Cycle,” was implemented among 42 students of the 4th grade at Madrasah Ibtidaiyah (MI) Masjid Al Akbar Surabaya. Effectiveness is determined by consideration of the effect and the normalized percentage gain value, while the hypothesis was tested using the Independent T-test. The results showed that the textbooks that were developed using multimodal-based science can improve the literacy skills of students. Based on the size of the effect size, textbooks developed with a multimodal approach were found effective in improving students' science literacy skills. The improvement occurred in all the competencies and knowledge of scientific literacy. The hypothesis testing showed that there was a significant difference in the ability of science literacy between the class that uses textbooks with multimodal-based and the class that uses the regular textbooks used in schools.